Development of bimetallic Ni-Cu/SiO2 catalysts for liquid phase selective hydrogenation of furfural to furfuryl alcohol - Patcharaporn Weerachawanasak; Pacharaporn Krawmanee; Weerachat Inkamhaeng; Francisco J. Cadete Santos Aires; Tawan Sooknoi; Joongjai Panpranot (My University, 2020)
Bimetallic Ni-Cu/SiO2 catalysts with different Cu loading (2–5 wt%) were developed for liquid phase selective hydrogenation of furfural to furfuryl alcohol. Among these, bimetallic 2%Ni-X%Cu/SiO2 (X = 2, 5) catalysts exhibited better catalytic performances than monometallic 2%Ni/SiO2 and 2%Cu/SiO2. Moreover, the bimetallic 2%Ni-5%Cu/SiO2 catalyst showed the best catalytic performance with 94% of furfural conversion and 64% of furfuryl alcohol selectivity. The synergetic effect of NiCu alloy particles that are present on bimetallic Ni-Cu/SiO2 catalysts change the adsorption configuration of furfural on the catalyst surface resulting in high catalytic performance in liquid phase selective hydrogenation of furfural to furfuryl alcohol.
Keywords: Furfuryl alcohol; Bimetallic strip; Catalysis for Biomass Conversion